What is a disappearing intra-abdominal mass? - Sahoo, Ashok Kumar; Goneppanavar, Mangala; Rajan, Susan; Raj, Raunak; N R, Vishnu Prasad (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Kumar Sahoo A, Goneppanavar M, Rajan S, Raj R, Prasad V. What is a disappearing intra-abdominal mass? Turk J Gastroenterol 2019; 30(9): 843-5.